BALA’ DAN MUSIBAH DALAM AL-QUR’AN (Studi Komparatif Tehadap Penafsiran M. Quraish Shihab dan Hamka dalam al-Tafsir al-Misbah dan al-Tafsir al-Azhar) - Alif Mardhotillah (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Scholars, interpreters, and the public have differing opinions regarding the understanding of bala' and musibah. This is because the word al-bala has various meanings. Some scholars say that bala' is a test. Others argue that bala' is a disaster. Similarly, with the word musibah, some scholars and the public interpret it as a disturbing event, while others say it is a trial bestowed upon His servants. These differences are due to the diverse meanings of the words bala' and musibah. Therefore, this researcher attempts to delve deeper into the words bala' and musibah by comparing two contemporary commentators to facilitate adaptation to our current era. Namely M. Quraish Shihab and Hamka. In this study, at least two things will be discussed. First, the interpretation of M. Quraish Shihab and Hamka about bala' and musibah. Second, the differences and similarities according to M. Quraish Shihab and Hamka about bala' and musibah. The approach of this research is library research, the type of research used is descriptive analysis, which aims to get a complete and clear picture of the problem that the researcher is studying, namely Bala' and Musibah in the Qur'an (Comparative Study of the Interpretation of M. Quraish Shihab and Hamka in al-Tafsir al-Misbah and al-Tafsir Azhar). The results of the study, Quraish Shihab and Hamka believe that this life is a test from AllahDisasters and calamities are considered an integral part of these trials, designed to test and refine human faith, patience, and obedience to Allah. They emphasize trust in Allah and gratitude in the face of disasters and calamities. The difference between the two views lies in their different emphases and explanations. M. Quraish Shihab focuses more on aspects such as trust in Allah and patience as positive responses in facing trials. Meanwhile, Hamka provides a more detailed explanation of how trust in Allah and patience can be demonstrated in the face of trials and tribulations.